Efficient extraction of ametryn in aqueous biphasic systems formed by polyethylene glycol and sodium sulfate - João O. Ferreira; Davi S.S. Souza; Giovana C. Zambuzi; Brenda S. Bega; Júlia S. Forster; Vinícius A.P. Tartare; Rafael C.R. Chagas; Adriano L. de Souza; Kelly R. Francisco (Results in Chemistry)
Ametryn is a triazinic herbicide widely used in sugarcane cultivation and poses environmental and health risks due to its toxicity and potential for bioaccumulation. This study explores the use of aqueous two-phase systems (ATPS) as a sustainable alternative for the extraction of ametryn from aqueous media. The ATPS, composed of poly(ethylene glycol) (PEG) 4000 g mol−1 and sodium sulfate at varying concentrations, were evaluated for their ability to partition 0.01 % (w/w) ametryn between the two phases at 298.15 K through intermolecular interactions. Five ATPS formulations with increasing concentrations of PEG and sodium sulfate were prepared: ATPS 1 to 5 contained (PEG/Na₂SO₄/water, (w/w%)) 8.75/7.68/83.57, 11.10/9.12/79.78, 12.80/10.05/77.16, 14.90/10.41/74.69, and 17.23/11.08/71.69, respectively. The extraction efficiency and partition coefficients (Kₚ) were determined for each system. ATPS 4 and 5 achieved 100 % extraction efficiency, outperforming conventional extraction systems such as octanol-water. The partition coefficients for ATPS 1, 2, and 3 were 4.07, 35.73, and 185.08, respectively, indicating a progressive enhancement in ametryn partitioning with increasing PEG and salt concentrations. Negative Gibbs free energy (ΔG) changes in all systems suggested thermodynamically favorable partitioning into the PEG-rich phase. This behavior is primarily attributed to hydrophobic and van der Waals interactions between ametryn and PEG, while the strong affinity of sodium sulfate for water limited its direct interaction with ametryn. These results demonstrate that PEG 4000/sodium sulfate-based ATPS represent an efficient, cost-effective, and environmentally friendly method for pesticide extraction, with potential for further optimization and application in environmental remediation near agricultural areas.